Indeterminate (B3) Breast Lesions and the Ongoing Role of Diagnostic Open Biopsy. (27th December 2021) - Tan, Elizabeth; Arachchi, Asiri; Cheng, Michael; Lockie, Darren
Abstract : Introduction . Due to their uncertain malignant potential, indeterminate breast lesions on core needle biopsy (CNB) require diagnostic open biopsy (DOB). This study evaluated DOB results given largely benign pathology. Lesions included are atypical papilloma, atypical ductal hyperplasia (ADH), atypical lobular hyperplasia (ALH), and radial scar/complex sclerosing lesions (RS/CSL). Methodology . A retrospective audit from 2010 to 2017 analysed patients with a screen-detected suspicious lesion and indeterminate (B3) CNB diagnosis. Primary outcome was the malignancy upgrade rate, with secondary evaluation of patient factors predictive of malignancy including age, symptoms, mammogram characteristics, lesion size, biopsy method, and past and family history. Results . 152 patients (median age 57 years) were included, with atypical papillomas being the largest subgroup (44.7%). On DOB histology, 99.34% were benign, resulting in a 0.66% malignancy upgrade rate. Patient characteristic analysis identified 86.84% of B3 lesions were in patients greater than 50 years old. 90.13% were asymptomatic, whilst 98.68% and 72.37% had a negative past and family history. Majority 46.71% of lesions had the mammogram characteristic of being a mass. However, with 57.89% of the lesion imaging size less than 4 mm, a corresponding 60.5% of core needle biopsies were performed stereotactically. The small malignant subgroup limited predictive factor evaluation. Conclusion . Albeit a low 0.66% malignancy upgrade rate in B3 lesions, no statistically significant patient predictive factors were identified. Until predictive factors and further assessment of vacuum-assisted excision (VAE) techniques evolve, DOB remains the standard of care.